A case–control–family study of idiopathic rapid eye movement sleep behavior disorder. Issue 4 (19th March 2019) - Liu, Yaping; Zhang, Jihui; Lam, Siu Ping; Zhou, Junying; Yu, Mandy Wai Man; Li, Shirley Xin; Chan, Joey Wing Yan; Postuma, Ronald B.; Mok, Vincent Chung Tong; Wing, Yun Kwok
Abstract : Objective: To determine the familial aggregation of idiopathic rapid eye movement sleep behavior disorder (iRBD), neurodegenerative diseases, and related biomarkers. Methods: A total of 404 and 387 first‐degree relatives of 102 patients with iRBD and of 89 controls were recruited, respectively. Among them, 204 and 208 relatives of patients and controls underwent face‐to‐face clinical assessment, whereas 97 and 75 relatives underwent further video‐polysomnographic assessment, respectively. Results: Compared with relatives of controls, relatives of patients demonstrated higher levels of RBD features, including chin tonic electromyography activity (mean = 1.5 ± 7.5 vs 0.3 ± 1.0, p  = 0.04) and behavioral events (n [weighted %] = 12 [11.3] vs 2 [1.9], adjusted hazard ratio [aHR] = 7.69, 95% confidence interval [CI] = 1.54–33.33, p  = 0.009) during rapid eye movement sleep, probable diagnosis (n [%] = 57 [14.9] vs 20 [4.9], aHR = 3.45, 95% CI = 1.96–6.25, p  < 0.001), and definite diagnosis (n [weighted %] = 10 [8.4] vs 2 [1.4], aHR = 5.56, 95% CI = 1.16–25.00, p  = 0.03). They also had higher risks of Parkinson disease (3.1% vs 0.5%, aHR = 5.88, 95% CI = 1.37–25.00, p  = 0.02), dementia (6.9% vs 2.6%, aHR = 2.44, 95% CI = 1.15–5.26, p  = 0.02), constipation (8.3% vs 2.4%, adjusted odds ratio = 4.21, 95% CI = 1.34–13.17, p  = 0.01), and motor dysfunction (Movement Disorders Society Unified Parkinson's Disease Rating Scale part III motor score, mean = 1.9 ± 3.2 vs 0.9 ± 2.3, p  = 0.002). The unaffected relatives of patients demonstrated a higher likelihood ratio of prodromal Parkinson disease (median [interquartile range] = 0.27 [1.19] vs 0.22 [0.51], p  = 0.03). Interpretation: iRBD is familially aggregated from isolated features to full‐blown sleep disorder. Relatives of patients carry a higher risk of alpha‐synucleinopathy in terms of neurodegenerative diseases and prodromal markers, suggesting a familial aggregation and staging pathology of alpha‐synucleinopathy. Ann Neurol 2019;85:582–592